Pendampingan Legalisasi Aset Wakaf di Desa Ringinsari Sumbermanjing Wetan Kabupaten Malang - Hosniyeh, Hosniyeh; Azizah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2026)
The main objective of this activity was to provide legal certainty, increase public understanding regarding waqf governance, and assist with the administrative process until the issuance of the waqf pledge deed. The methods used included waqf asset data collection, interviews with village officials and waqifs, legal assistance, preparation of administrative documents, and facilitation of the waqf pledge with the Waqf Pledge Deed Making Official (PPAIW). The results of the activity showed that one waqf asset belonging to the Nurul Iman Mosque successfully went through the waqf pledge process and obtained an official deed recognized by the state. This activity also raised public awareness about the importance of waqf legalization to protect assets and ensure their use is in accordance with sharia principles. Based on these findings, similar activities need to be replicated in other areas facing waqf legality issues, and ongoing support is needed to enable communities to manage waqf assets professionally, transparently, and oriented towards community welfare.